Unusual Occurrence of Tongue Sensorial Disorder after Conservative Surgical Treatment of Lymphoepithelial Cyst - Luane Macêdo de Sousa; Assis Felipe Medeiros Albuquerque; Paulo Goberlânio Barros Silva; Thâmara Manoela Marinho Bezerra; Ealber Carvalho Macedo Luna; Filipe Nobre Chaves; Francisco Samuel Rodrigues Carvalho; Karuza Maria Alves Pereira; Ana Paula Negreiros Nunes Alves; Thyciana Rodrigues Ribeiro; Fábio Wildson Gurgel Costa (Hindawi Limited, 2015)
Lymphoepithelial cyst is a rare lesion of the oral cavity, with the mouth floor being the most common site of occurrence. The therapeutic approach of choice is the surgical treatment, which has rare cases of postoperative complications. The aim of this study is to report the case of a 53-year-old patient who came to Dental Service in the Federal University of Ceará complaining of a small nodular lesion (0.5 cm) located in the ventral tongue. Excisional biopsy was performed and the surgical specimen was submitted for anatomopathological analysis, which found that there was an oral lymphoepithelial cyst. The patient returned after seven days for suture removal and reported loss of sensitivity around the ventral tongue. We prescribed Citoneurin for ten days; however, there was not any significant improvement of the sensitivity. Low frequency laser therapy sessions were applied. The only postoperative symptom was dysesthesia, where there is only a sensitivity decrease. Currently, the patient has a postoperative period of 1 year without recurrence of the lesion. Although previous reports have no described tongue sensorineural disorders associated with this lesion, the occurrence of this event may be related to an unexpected anatomical variation of the lingual nerve.